Examination of the diversity of indoor molds in a Hungarian student hostel - Varga, János (Acta Biologica Szegediensis, 2013)
Molds are widely distributed in indoor and outdoor environments. They are common in household dust and can cause allergic symptoms or invasive infections in humans with weak immune system. They can also be harmful through their toxin producing abilities. Our aim was to examine the diversity of indoor molds in a student hostel. Isolation of the samples was carried out using standard dichloran-glycerol media. After purification, the isolates were identified by ITS sequence analysis and morphological traits. Samples were collected from different places of the kitchen, the bathroom and the living room during the summer (in August), and during late autumn (in November). The most frequently identified genera were Aspergillus, Alternaria, Cladosporium, Penicillium and Aureobasidium. A high diversity was observed at the species level based both on the sampling location and the season. In general, more species were recovered during the summer period than during November. A similar trend was observed when the number of Aspergillus species were compared: more species were recovered during summer than in November. High numbers of Eurotium and Aureobasidium isolates were detectable in the summer sample set, whereas the samples collected in November did not contain any of these species. On the contrary, the frequency of Alternaria, Cladosporium and Penicillium isolates did not differ significantly between the two sampling periods. Further studies are in progress to examine the diversity of indoor molds in other seasons and in other locations.